Couple Satisfaction, Depressive Symptoms, and the Therapeutic Alliance: A Systemic Perspective. Issue 2 (27th September 2020) - Wu, Qiong; Parker, Michele L.; McWey, Lenore M.; Ledermann, Thomas
Abstract : There is a well‐established bidirectional, negative association between couple satisfaction and depressive symptoms. Yet, a family systems perspective emphasizes the role of the therapist in interrupting this recursive cycle between couple satisfaction and depressive symptoms. The current study utilized longitudinal data to explore the bidirectional associations between depressive symptoms and couple satisfaction, moderated by the therapeutic alliance over the course of therapy. The study included 108 couples participating in couple therapy at a university training clinic. Couples rated their depressive symptoms and couple satisfaction separately before the intake session and at the end of the fourth session, and they also reported their individual therapeutic alliance with the therapist at the end of the second and third sessions. Actor‐partner interdependence moderation model analysis revealed several moderation effects. In general, with low therapeutic alliance, couples with higher initial symptoms (such as depressive symptoms and low couple satisfaction) reported more severe symptoms at the fourth session, compared to those who had fewer initial symptoms. The moderating effect of alliance on a couple's symptoms was found both among individuals, and between partners. Systemic clinical implications and suggestions for future research are discussed. Resumen: Hay una asociación bidireccional y negativa firmemente establecida entre la satisfacción en la pareja y los síntomas depresivos. Sin embargo, la perspectiva de sistemas familiares enfatiza el papel que desempeña el terapeuta en la interrupción de este ciclo recurrente entre la satisfacción en la pareja y los síntomas depresivos. El presente estudio utilizó datos longitudinales para analizar las asociaciones bidireccionales entre los síntomas depresivos y la satisfacción en la pareja, moderadas por la alianza terapéutica durante el transcurso de la terapia. El estudio incluyó 108 parejas que participaron en terapia de pareja en una clínica universitaria de formación. Las parejas calificaron sus síntomas depresivos y la satisfacción en la pareja por separado antes de la sesión de ingreso y al final de la cuarta sesión, y también informaron su alianza terapéutica individual con el terapeuta al final de la segunda y la tercera sesión. El análisis del modelo de moderación de la interdependencia entre el actor y la pareja reveló varios efectos de la moderación. En general, con una alianza terapéutica baja, las parejas con síntomas iniciales más altos (como síntomas depresivos y baja satisfacción en la pareja) informaron síntomas más intensos en la cuarta sesión en comparación con aquellos que tenían menos síntomas iniciales. El efecto moderador de la alianza en los síntomas de la pareja se halló tanto entre las personas como entre las parejas. Se debaten las consecuencias clínicas sistémicas y las sugerencias para futuras investigaciones. 摘要: 伴侣满意度和抑郁症状之间存在一种明确的双向负相关关系。然而，家庭系统的观点强调治疗师的干预作用，因为治疗师可以打破伴侣满意度和抑郁症状之间的反复循环。本研究利用纵向数据来探索抑郁症状和伴侣满意度之间的双向联系，这种相关性受到治疗过程中建立起来的治疗联盟的调节影响。这项研究包括了108对在大学培训诊所接受伴侣治疗的伴侣。在接受治疗前和第四次治疗结束这两个时间点，伴侣们分别评估了他们的抑郁症状和夫妻满意度，在第二和第三次治疗结束时，他们也报告了他们与治疗师的个人治疗联盟。主导行为者‐对象相互依赖调节模型分析揭示了几种调节效应。一般来说，在治疗联盟度较低的情况下，与初始症状较少的夫妻相比，初始症状较高的夫妻（如抑郁症状和伴侣满意度较低）在第四次治疗时报告的症状更严重。无论是在个体之间，还是在伴侣之间，都发现联盟对夫妻症状的调节作用。本文讨论了系统性的临床意义和对未来研究的建议。